Boletín y Elegía de las Mitas de César Dávila Andrade como Recurso Didáctico para el Desarrollo de la Comprensión Lectora - Layedra Bustamante, Cielo Anayelhy (2024)
The present research is called “Boletín y Elegía de las Mitas de César Dávila Andrade as a didactic resource for the development of reading comprehension”. It aimed to determine the didactic and symbolic capacity of the classic of Ecuadorian poetry to become a resource that develops reading comprehension in the students of the tenth grade parallel "E" of the "Juan de Velasco" Educational Institution. A questionnaire was applied through a descriptive-level and quantitative approach. It was based on the reading comprehension of the poem called “Boletín y Elegía de las Mitas de César Dávila Andrade”. The data was collected from a sample of 31 students who belong to the tenth grade parallel "E". It was determined that the poem favored the development of reading comprehension within the students’ sample due to its enriched content of a testimonial narrative genre. It also provided a great valuable impact on the students by motivating their interest in reading for the understanding of the text at a critical, intertextual, and global level. The results emphasized that the poem stimulated the imagination and promoted the development of reflection and interpretation. It also concluded that it was necessary to use a didactic resource to motivate and captivate the attention of the students. This way, it helped to strengthen different skills in the students which had an important contribution to their academic success. The research ended with an outstanding result and a positive influence on the students. It allowed the students to improve their reading comprehension and encouraged their interest in learning in a literary way that addresses the history of our roots, identity, and legacy of Ecuadorian literature.